Factors that affect training effectiveness of non-executive level employees at Transmission Operations Division, Segamat Operation Centre, Petronas Gas Berhad / Siti Nur Aisyah Baharun - Baharun, Siti Nur Aisyah (2010)
Training is a planned process to modify attitude, knowledge, skill, behavior through learning to acquire effective performance in an activity on range of activities. Effectiveness means producing an intended result. The HR manager must really outline the required training programs that focus to the outcomes as well as measure the effectiveness of the training. The effectiveness of training is very important factor. Factors that contribute to the training effectiveness must be put into serious consideration so that the amount invested into training is benefited. Lack of interest and were forced to attend training program are some of the problems that the company faced. The past researcher shows that there are many factors that affect training effectiveness. Present research study on three factors that could be the factors that affect training effectiveness which are working environment, training methods and trainee’s characteristics. This study has been conducted within Transmission Operations Division (TOD), Segamat Operation Centre (SOC), PETRONAS Gas Berhad (PGB) and it involved 44 respondents in different department. Results of the present study showed that the most influential factors that affect training effectiveness at TOD, SOC, PGB are working environment and trainee’s characteristics. It also shows that working environment and trainee’s characteristics have positive correlation relationship with training effectiveness within TOD, SOC, PGB. Recommendations for future research are also have been discussed.